Elizabeth Castro on EPUB - Castro, Elizabeth (Peachpit Press, 2013)
Elizabeth explains that InDesign's robust EPUB export features takes advantage of all the things you've already done for a print product. Although the exported EPUB file is a good start there are things that InDesign doesn't do that well. She goes on to explain that by opening the file in a powerful text editor you can unzip the EPUB and see and edit the files. The video interview goes on to talk about best practices, fixed layouts, EPUB to MOBI (Kindle) conversion strategies, fonts, indexes, and testing EPUB/MOBI files.